STRATEGY FOR A LOCAL SINGAPOREAN FIRM TO ATTAIN COMPETITIVE ADVANTAGE - NANGIA, KARUN (2007)
Continuous improvements in technology are resulting in a growing number of new imaging diagnostic tests that combine accuracy and speed bundled together, fuelled by the extensive use of computers in this digital era of computing. Though mammography is the traditional method employed in breast screening, new techniques like infrared imaging technology are being evolved to diagnose the cancerous growth.